Pemphigus foliaceus in a dog – Clinical, cytopathological and histopathological relation (Research, Society and Development, 2022)
Pemphigus foliaceus is an autoimmune dermatosis characterized by vesicobullous, pustular and crusted skin lesions resulting from acantholysis process. Diagnosis is based on animal history, physical evaluation, cytopathological analysis and confirmed by histopathology. The present study aimed to describe the clinical presentation, and cytological and histopathological findings in the diagnosis of pemphigus foliaceus in a 9-year-old male German Shepherd dog, presented at Hospital de Clínicas Veterinárias of the Federal University of Pelotas. Dermatological examination revealed generalized alopecia and seborrhea, crusts on dorsum, presence of deep pyoderma, hyperkeratosis, nodular and plaque lesions in the ventral cervical and left lateral thoracic regions. There were crusted and alopecic lesions around nasal planum. Crust and vesicobullous lesions were also observed in the ears bilaterally, both internal and externally, seropurulent exudate in the left ear and purulent in the right ear. Cytological evaluation showed the presence of acantholytic keratinocytes and the diagnosis of pemphigus foliaceus can be confirmed by histopathology. This report shows the importance of the cytopathological evaluation in the diagnostic screening of pemphigus foliaceus, since clinical assessment in association with cytology provided key points for diagnosis, with further confirmation by histopathology, which is the gold standard exam.